2011
DOI: 10.5551/jat.8722
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Fractalkine (CX3CL1) and CX3CR1+CD4+ T Cells with Common Carotid Artery Intima-Media Thickness in Patients with Chronic Kidney Disease

Abstract: CKD subjects showed an increase in CD4(+)CX3CR1(+) T cell population, plasma fractalkine and IMT; the association of CD4(+)CX3CR1(+) T cells and plasma fractalkine with CCA-IMT indicates that the fractalkine-CX3CR1 pathway may be important in the development and/or progression of atherosclerosis in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…44 Increased T cell CX3CR1 in CKD has previously been associated with carotid intima-media thickness. 45 Also in our experiments, aortic T cells upregulated CX3CR1. Beyond this, adoptive transfer of CX3CR1-competent T cells into LDLr…”
Section: Cx3cr1 + T Cells Promote Atherosclerotic Inflammation In Renmentioning
confidence: 71%
“…44 Increased T cell CX3CR1 in CKD has previously been associated with carotid intima-media thickness. 45 Also in our experiments, aortic T cells upregulated CX3CR1. Beyond this, adoptive transfer of CX3CR1-competent T cells into LDLr…”
Section: Cx3cr1 + T Cells Promote Atherosclerotic Inflammation In Renmentioning
confidence: 71%
“…In patients with RA [59], end-stage renal disease (ESRD) [60], chronic kidney disease [61], type 2 diabetes [62], or human immunodeficiency virus (HIV) infection [63], CD4 + CD28 -T cells were found to be associated with atherosclerosis, suggesting that CD4 + CD28 -T cells take part in vascular plaque destabilization and rupture in patients with inflammatory disorders.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The authors observed significantly elevated levels of soluble CX3CL1 in patients with carotid artery stenosis near occlusion (90%-99% stenosis) but similar levels among patients with moderate (50%-70% stenosis) and advanced (70%-90% stenosis) carotid artery disease [23] . Yadav et al assessed 62 healthy controls and 128 patients with stage III-V chronic kidney disease (CKD) [33,34] . The authors observed increased levels of soluble CX3CL1 in CKD subjects and a significant correlation between common carotid artery intima-media thickness and soluble CX3CL1 levels.…”
Section: Cx3cl1 and Atherosclerosis: Clinical Researchmentioning
confidence: 99%